Self-Medication and Associated Factors Among Pregnant Women Attending Antenatal Care at Kemisie General Hospital, North East Ethiopia - Tuha, Abdu (Patient Prefer Adherence, 2020)
INTRODUCTION: Self-medication is an important part of daily self-care, without the supervision of health professionals. It is commonly practiced by pregnant women all over the world and may result in maternal and fetal risks. Hence, this study assessed self-medication practices and associated factors among pregnant women attending Kemisie General Hospital. METHODS: A facility-based cross-sectional study was conducted using a structured questionnaire on pregnant women who were attending antenatal care at Kemisie General Hospital. A simple random sampling technique was employed to select the study participants. Descriptive and inferential statistics were computed using the Statistical Package for Social Sciences version 20. RESULTS: Among 223 pregnant women, 60 (26.9%; 95% CI: 20.9%, 32.9%) and 111 (48.9%; 95% CI: 43%, 58%) practiced self-medication on conventional and herbal medicine, respectively. The predictors of self-medication of conventional medicine among pregnant women were prior experience to the drug (P-value: 0.00, AOR=126.04, 95% CI: 32.55–488.04) and no pervious history of abortion (P-value: 0.00, AOR=0.01,95% CI:0.002–0.04), while college educational level (P-value: 0.00, AOR=13.45,95%, CI: 3.58–50.5), history prior herbal medicine use (P-value: 0.00, AOR=9, 95% CI: 3.32–24.39), Ruta chalepensis (P-value:0.001,AOR=193.7,95% CI:8.64–4342.1) and Ocimum lamiifolium type of herb use (P-value: 0.004, AOR=12.72, 95% CI: 2.27–71.38), and 5–10km health facility distance (P-value:0.022, AOR=0.1, 95% CI: 0.01–0.73) were predictors for self-medication practice of herbal medicines among pregnant women. CONCLUSION: Nearly one-third and two-third of pregnant women practiced self-medication on conventional and herbal medicine, respectively. Prior experience to the drug and no previous history of abortion associated with self-medication of conventional medicine, while college educational level, history prior herbal medicine use, Ruta chalepensis and, Ocimum lamiifolium type of herb use, and 5–10km distance were predictors for self-medication practice of herbal medicines. Improving health service coverage and awareness creation on rational medication use is recommended to prevent fetal and maternal risks.